Synthesis, structural studies and ligand influence on the stability of aryl-NHC stabilised trimethylaluminium complexes - Wu, Melissa M. (2016)
Treatment of a series of aromatic NHCs (IMes, SIMes, IPr and SIPr) with trimethylaluminium produced their corresponding Lewis acid–base adducts: IMes·AlMe3 (1), SIMes·AlMe3 (2), IPr·AlMe3 (3), and SIPr·AlMe3 (4). These complexes expand the few known examples of saturated NHC stabilised Group 13 complexes. Furthermore, compounds 1–4 show differential stability depending on the nature of the NHC ligand. Analyses of topographic steric maps and NHC %VBur were used to explain these differences. All the compounds have been fully characterised by multinuclear NMR spectroscopy, IR and single crystal X-ray analysis together with computational studies.